A Checklist of Elephant Movement Paths/corridors in Mahanadi Catchment, Orissa - Sar, C. K.; Lahiri-Choudhury, D. K. (Indian Forester, 2002)
Orissa has an estimated population of 1,827 elephants, which is a reduction 10.6% from the estimate of 1979. This could be due to loss and degradation of habitat and corridor. A study of 7 forest divisions from 1997 June to 1999 March in the Mahanadi catchment identified five major crossing points used by herds/family groups across the river Mahanadi as well as four similar crossing points across highways running parallel to the river. The study shows that during 1979 to 1999, the elephant population on the South bank (in 2 FDs) decreased by 70.59%, whereas on the North bank (in 5 FDs) it increased by 85.94%. Attention is needed to protect its habitat on the South bank and the habitat on both the sides of the river crossing points.